1999
DOI: 10.2337/diacare.22.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leptin concentrations in Pima Indians living in drastically different environments.

Abstract: These results suggest that independent of body composition, leptin concentration may be increased by environmental factors, such as a high-carbohydrate diet and a high level of physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 0 publications
1
35
0
2
Order By: Relevance
“…Interestingly, our results show that fasting plasma leptin concentrations fell during MUFA-rich periods. Plasma leptin is an important signal for regulation of energy stores and has been associated with improved insulin action (32,33), and its concentrations seems to be increased by high-CHO diets (34). However, this finding should be interpreted with caution because elevated leptin concentrations in the context of obesity are generally viewed as evidence for leptin resistance and insulin resistance (35).…”
Section: Effects Of Macronutrient Diet Composition On Energy Balancementioning
confidence: 71%
“…Interestingly, our results show that fasting plasma leptin concentrations fell during MUFA-rich periods. Plasma leptin is an important signal for regulation of energy stores and has been associated with improved insulin action (32,33), and its concentrations seems to be increased by high-CHO diets (34). However, this finding should be interpreted with caution because elevated leptin concentrations in the context of obesity are generally viewed as evidence for leptin resistance and insulin resistance (35).…”
Section: Effects Of Macronutrient Diet Composition On Energy Balancementioning
confidence: 71%
“…A number of epidemiological studies examined serum leptin concentration in diabetic and non-diabetic subject. For example, among US Pima Indians, subjects suffering from type 2 diabetes had lower leptin concentrations than non-diabetic subjects, independently of percentage body fat (Fox et al, 1999). Even if it has been discussed previously that insulin resistance associated with GMD results in increased leptin secretion , Utriainen et al, 1996, the prognosis of GMD patients in respect to type 2 diabetes still remains unclear.…”
Section: Resul Resul Resul Resul Results T T T Ts S S S S Borderline Smentioning
confidence: 96%
“…An increase in energy efficiency mediated by low leptin prolongs longevity in Lep ob/ϩ mice (60). Studies have suggested that low leptin may precede adiposity in primates and some indigenous human populations, but these results have not been confirmed by others (62)(63)(64)(65)(66).…”
Section: Role Of Leptin In Famine and Feastmentioning
confidence: 96%